Assessment of the soil-erosion-sediment for sustainable development of South America. (1st November 2022) - Riquetti, Nelva B.; Mello, Carlos R.; Leandro, Diuliana; Guzman, Jorge A.; Beskow, Samuel
Abstract: One of the greatest threats to maintaining sustainable agro-ecosystems is mitigating the episodic soil loss from farm operations, further exacerbated by meteorological extremes. The Revised Universal Soil Loss Equation (RUSLE) is a model that combines the effects of rain, soil erodibility, topography, land cover, and conservation practices for estimating the annual average soil losses. This study aims to quantify soil water erosion to continental South America (S.A.) through RUSLE using available datasets and characterizing the average sediment delivery rate (SDR) to the major S.A. basins. Soil erodibility was estimated from the Global Gridded Soil Information soil database. LS-factor's topographical parameter was derived from Digital Elevation Models using the "Shuttle Radar Topography Mission" dataset. The R-factor was estimated from a previous study developed for S.A. and the C-factor from the Global Land Cover (Copernicus Global Land Services) database. We used a modeling study for SDR that simulated the annual average sediment transport in 27 basins in S.A. RUSLE set up presented a satisfactory performance compared to other applications on a continental scale with an estimated averaged soil loss for S.A. of 3.8 t ha −1 year −1 . Chile (>20.0 t ha −1 year −1 ) and Colombia (8.1 t ha −1 year −1 ) showed the highest soil loss. Regarding SDR, Suriname, French Guyana, and Guyana presented the lowest values (<1.0 t ha −1 year −1 ). The highest soil losses were found in the Andes Cordillera of Colombia and the Center-South Region of Chile. In the former, the combination of "high" K-factor, "very high" C-factor, and "very high" LS-factor were the leading causes. In the latter, agriculture, livestock, deforestation, and aggressive R-factor explained the high soil loss. Basins with the highest SDR were located in the North Argentina – South Atlantic basin (27.73%), Mar Chiquitita (2.66%), Amazon River basin (2.32%), Magdalena (2.14%) (in Andes Cordillera), and Orinoco (1.83%). Highlights: Water erosion is one of the most relevant impacts on sustainable food production. South America (S.A.) shelters several biomes and landscapes on the earth planet. Countries in S.A. are highly dependent on agricultural and livestock for their GPD. RUSLE was set up for the first time in all S.A. to identify critical erosion areas. Planning and management of the soils are fundamental for a cleaner production.